Information and society - Buckland, Michael (Massachusetts : MIT Press, 2017)
"A concise, informal account of the ways in which information and society are related, and of our ever-increasing dependence on a complex multiplicity of messages, records, documents, and data."
Includes bibliographical references and index.
Keywords: Information science -- Sociological aspects; Communication -- Social aspects; Documentation -- Social aspects; Information society